Viabilidade técnica e econômica dos sistemas construtivos: elementos pré-fabricados, paredes de concreto e alvenaria estrutural de habitações residenciais populares - Reis, Leonardo Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Por conta do atual cenário do Brasil, com números altos de desigualdade social, que por dados, um alto número da população ainda não tem acesso à casa própria e falta de acesso a recursos financeiros compatíveis, visamos neste trabalho, buscar por meio de uma análise de sistema construtivo como alvenaria estrutural, casas com paredes de concreto e casas de elementos pré-fabricados capaz de diminuir o valor final de empreendimentos residenciais unifamiliares populares, com base em conhecimentos adquiridos ao longo de um ano e meio de estágio em obras, além do uso de bancos de dados eficientes para nos embasar melhor no planejamento físico-financeiro para execução destes projetos além da elaboração de cronograma físico da obra.

Due to the current scenario in Brazil, with high numbers of social inequality, which according to data, a high number of the population still does not have access to their own home and lack of access to compatible financial resources, we aim in this work, to seek through an analysis construction system such as structural masonry, houses with concrete walls and houses made of prefabricated elements capable of reducing the final value of popular single-family residential developments, based on knowledge acquired over a year and a half of internship in construction, in addition to the use of efficient databases to better support us in the physical-financial planning for the execution of these projects in addition to preparing the physical schedule for the work.
Technical and economic feasibility of construction systems: prefabricated elements, concrete walls and structural masonry of popular residential housing
Keywords: Alvenaria Estrutural; Paredes de Concreto; Pré-fabricados; Structural masonry; Prefabricated.; Concrete walls